Expert System Application for Identifying Formalin and Borax in Foods Using the Certainty Factor Method. Issue 6 (2018) - Sudrajat, Dadang; Daengs, G.S. Achmad; Satria, Erwinsyah; Nurmawati, N.; Iskandar, Akbar; Khasanah, K.; Sururi, Ahmad; Rahim, R.
No abstract available